Evaluation of essential oils against postharvest pathogens of papaya - Sai Kavya, V; Naga Lakshmi, T; Narasimha Rao, S; Sunitha, P; Sudha Vani, V (Indian Journal of Plant Protection, 2024)
Antifungal efficacy of five essential oils viz., basil, cinnamon, clove, pepper mint and thyme was studied both in vitro and in vivo to know the effect for the management of postharvest pathogens of papaya. Colletotrichum gloeosporioides, Fusarium oxysporum and Aspergillus niger were isolated from the infected fruits by tissue culture isolation. In vitro studies of five essential oils with four concentrations showed significant effect to inhibit the mycelial growth. Among the essential oils, under in vitro conditions thyme @ 1000 ppm, and cinnamon @ 1000 ppm, thyme @ 500,750 and 1000 ppm, pepper mint and clove @ 1000 ppm and thyme at all the concentrations completely inhibited (100%) the mycelial growth of C. gloeosporioides, F. oxysporum and A. niger, respectively. Under in vivo conditions, thyme @1000ppm was found to be effective and inhibited the postharvest pathogens of papaya.